Post-operative complications of ilizarov technique in tibial non-union- A prospective study - Uddin, K M Badar; Khan, Md Rukanuddawla; Chakraborty, Swarupananda; Nath, Asho Tosh; Mahmood, Sheikh Kawsar; Mazher, Khandoker Muhammud; Chowdhury, A K M Anisuzzaman (Journal of Dhaka National Medical College & Hospital, 2024)
Background: Non-union of the tibia is a significant problem for patient and surgeon, and in many situations the patient has undergone more than one surgical procedure, and lost considerable time from his job and his life. Ilizarov technique is an effective method for treatment of tibial non-union. It has low rate of complication. Objective: To assess the post-operative complications of Ilizarov technique in tibial non-union. Methodology: This prospective study was carried out at the Department of Orthopedic Surgery at Chittagong Medical College Hospital, Chittagong from June 25, 2018 to June 24, 2019. All the data were compiled and sorted properly and the quantitative data was analyzed statistically by using Statistical Package for Social Science. Result: out of 12 cases, 8 (66.7%) were in <30 years age group. Mean (±SD) age was 27.58±5.62 years. Eleven cases (91.7%) in the study were male and only 1 case (8.3%) was female. Operation was performed in most of the cases (41.7%) in less than 2 hours and in 25% of them it was more than 3 hours. 91% had corticotomy during operation. No major neuro-vascular structures injury was observed during surgery. In majority of the cases (n=8) external fixator held for a time period of 7-8 months. In 2 cases fixator was held for 6 months and in other 2 cases it was held for 10 months. Most common complication was pin site infection observed in 66.7% patients followed by wire breakage (16.7%) and persistent infection (8.3%). 25% patients developed no complication. Conclusion: Awareness of predictable complications is beneficial to prevent or early detection of the expected complication which can improve the risk-benefit balance. J. Dhaka National Med. Coll. Hos. 2024; 30 (02): 33-35